Perkembangan Ekonomi Digital Mengenai Perilaku Pengguna Media Sosial Dalam Melakukan Transaksi - Danang Rifai; Sania Fitri; Irma Nirmala Ramadhan (ADI Bisnis Digital Interdisiplin Jurnal, 2022)
The development of the digital economy is related to the behavior of social network users in transactions. The rapid development of information technology and telecommunications has a significant impact on consumer behavior in the world, selection and purchase decisions. Information technology makes it possible to carry out various activities quickly, accurately, without time and place restrictions, so that it is expected to increase efficiency and productivity. Changes in consumer behavior regarding the way in which information is collected and the buying and selling transactions carried out must continue to be examined to obtain accurate information about consumer wants and needs. In Indonesia, it has the potential to influence the development of the technology world. Technological developments have emerged in various types of fields, especially in the development of the digital economy. The digital economy has both positive and negative impacts on Indonesia's development. The Impact of the Development of the Digital Economy has become a separate platform for the government or the community to become a forum for carrying out various types of economic transactions. The purpose of this study is to analyze the impact of the development of the digital economy on social media users in conducting transactions. The result of this research is the development of advertising companies, and many online companies or businesses are implementing sales promotions on social networks for their products, so it is very helpful in promoting and expanding the audience.